Versailles Meets the Taj Mahal : François Bernier, Marguerite de La Sablière, and enlightening conversations in seventeenth-century France - Beasley, Faith Evelyn (University of Toronto Press, 2018)
Challenging the prevailing images of India derived from nineteenth-century "orientalism", Versailles Meets the Taj Mahal identifies and explores the traces that exposure to India left on the cultural artifacts and mindset of France's "Great Century."